Negative impact of SARS-CoV-2 infection in acute coronary syndrome mortality in a Latin American cohort study - Junior, Wenderval Borges Carvalho; Ferreia, Neila Nunes; Santos, Luciano de Moura; Borges, Patrícia Brito de Almeida; Albuquerque, Cleandro Pires de; Espindola, Laila Salmen; Nóbrega, Otávio de Toledo; Gomes, Ciro Martins; Mota, Licia Maria Henrique da; Soares, Alexandre Anderson de Sousa Munhoz (Frontiers in Medicine, 2022)
Purpose COVID-19 infection has been associated with a high risk of complications and death among patients with acute coronary syndrome (ACS). However, there is little information on the simultaneous involvement in Latin American countries. Methods In the period between May 2020 and February 2021, an observational, longitudinal, prospective cohort study with two parallel branches was conducted in private and public hospitals in Brasilia, Brazil, including patients with ACS with and without a positive SARS-CoV-2 test result during hospitalization. Results A total of 149 patients with ACS were included (75 with COVID-19 and 74 controls). Patients with COVID-19 exhibited an average of 62 years of age, 57% men, 40% diabetics, 67% hypertensive, 48% had an ACS with ST-segment elevation, Killip I was predominant, a low Syntax Score in 72%, with an average Grace Score of 117, and a length of hospitalization of 43 days in average. The control branch was similar in clinical characteristics, except for a lower proportion of ST-segment elevation ACS (16%, p < 0.01) and a higher incidence of arrhythmias (8 vs. 20 %, p = 0.03). Using the Cox regression method of analysis of covariates collected in the study, it was identified that patients with COVID-19 had a risk of death 2.34 times higher than patients without COVID-19 (p = 0.049). Conclusion In this study conducted in a Latin American capital, SARS-CoV-2 infection predicted a higher chance of death in patients admitted with ACS, which is a finding that reinforces the need for greater care when diseases develop in overlapping ways.